2009
DOI: 10.1007/s11596-009-0522-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between RASSF1 gene polymorphisms and lung cancer susceptibility among people in Hubei Province of China

Abstract: The relationship between Ala/Ser polymorphism in 133 codon of exon 3 region of the RASSF1 gene and genetic susceptibility of lung cancer in Hubei province Han population was investigated by a case-control study. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique was adopted to analyze the polymorphism of codon 133 of exon 3 in the RASSF1 gene of 100 pathologically diagnosed lung cancer patients, and 100 healthy controls. The relationship between different genotypes and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Mechanistic toxicity studies revealed that heavy metals such as cadmium, copper, and lanthanum could damage liver and gill tissue and act as antioxidants (Yin 2014; Zhang et al 2014; Jiang et al 2015a; Hua 2017). In the case of biocides, it is known that cypermethrin, fenvalerate, and chlorpyrifos damage the nervous system of various fish species, causing loss of equilibrium that may lead to death (Cao 2010; Jiang et al 2015b; Wang 2017). However, those neurotoxicants lose their specific activity in embryos and larvae with immature nervous systems (Yamagami 1981; Sobanska et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic toxicity studies revealed that heavy metals such as cadmium, copper, and lanthanum could damage liver and gill tissue and act as antioxidants (Yin 2014; Zhang et al 2014; Jiang et al 2015a; Hua 2017). In the case of biocides, it is known that cypermethrin, fenvalerate, and chlorpyrifos damage the nervous system of various fish species, causing loss of equilibrium that may lead to death (Cao 2010; Jiang et al 2015b; Wang 2017). However, those neurotoxicants lose their specific activity in embryos and larvae with immature nervous systems (Yamagami 1981; Sobanska et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a total of 14 case-control studies including 4572 cases and 4320 controls were analyzed in this meta-analysis (Schagdarsurengin et al, 2005;Kanzaki et al, 2006;Gao et. al, 2008;Xiao et al 2009;Bergqvist et al, 2010;Donninger et al, 2011;Bayram, 2012;Kawai et al 2012;Meyer et al, 2013;Zhou et al, 2013). The characteristics of selected studies are summarized in Table 1.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…The sample size in these case-control studies varied considerably (range . All studies were case-control studies, including four breast cancer studies (Schagdarsurengin et al, 2005;Gao et al, 2008;Bergqvist et al, 2010;Donninger et al, 2011), two lung cancer studies (Kanzaki et al, 2006;Xiao et al 2009), two esophageal squamous cell carcinoma (ESCC) studies (Kanzaki et al, 2006;Zhou et al, 2013), and the others including colorectal cancer (Kanzaki et al, 2006), head and neck cancer (Kanzaki et al, 2006), renal cell carcinoma (Kawai et al 2012), hepatocellular carcinoma (Bayram, 2012), gastric cancer (Zhou et al, 2013), prostate cancer (Meyer et al, 2013). 8 studies conducted in the Asian population, 5 in Caucasian population, and 1 in mixed population.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…The most widespread form of human genetic variation is single nucleotide polymorphism (SNP), which may contribute to tumor sensitivity. To date, many studies have demonstrated that SNPs of RASSF1A are associated with the risk of many types of cancers, including breast cancer ( 12 - 15 ), lung cancer ( 16 , 17 ), esophageal cancer ( 16 , 18 ), head and neck cancer ( 16 ), colorectal cancer ( 16 ), renal cell carcinoma ( 19 ), HCC ( 20 ), gastric cancer ( 18 ), and prostate cancer ( 21 ). It has been proven that guanine (G)/thymine (T) SNP at the first position of codon 133 in exon 3 of RASSF1A (dbSNP ID: rs2073498), leads to the replacement of an Ala residue (GCT) through the Ser residue (TCT) in the ataxia telangiectasia mutated (ATM) phosphorylated position, and can impact the function of RASSF1A ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%